PENGARUH PENGGUNAAN BAHAN AJAR BERBASIS MULTIMEDIA TERHADAP MINAT BELAJAR SISWA SEKOLAH DASAR - Alfia Dwi Saputri; Fery Andria Riski; Rizkia Amelia; Shalma As’ari; Satria Wicaksana; Zulfadewina (STKIP Subang, 2025)
This systematic literature review examines the influence of multimedia-based teaching materials on elementary school students' learning interest. The digital revolution has fundamentally transformed educational landscapes, yet research specifically addressing multimedia's impact on affective dimensions of learning remains limited. This study employed a systematic literature review approach following PRISMA protocol, analyzing peer-reviewed studies published between 2021-2025 across five major academic databases. Findings reveal that multimedia teaching materials significantly enhance learning interest when they incorporate high interactivity, content personalization, immediate feedback, and visually engaging elements relevant to students' daily experiences. The review identified that multimedia resources effectively accommodate diverse learning styles, stimulate multisensory engagement, and create more contextual learning experiences compared to conventional materials. Implementation challenges include digital infrastructure disparities, pedagogical adaptation requirements, and the need for teacher capacity building. This research contributes valuable insights for educators and policymakers seeking to leverage multimedia technologies to foster more engaging and effective learning environments for elementary students in the digital era.